Timing measurements for a parallel Newton-Raphson load flow program for a cluster of workstations - Uy, Roberto; Ramos, Manuel L. Jr.
This paper presents an alternative implementation of the Newton-Raphson power flow suitable for commodity clusters that utilizes widely available software components. The components used are specified and the data decomposition along with the changes to the power flow formulation to be more suitable to run on a cluster is described. Timing measurements for the power flow computation and the overall execution time are used to show the values of speedup obtained as the provided input sizes and number of processors is varied.
Keywords: Power flow